Are Caudal Blocks for Pain Control Safe in Children? An Analysis of 18, 650 Caudal Blocks from the Pediatric Regional Anesthesia Network (PRAN) Database. (January 2015) - Suresh, Santhanam; Long, Justin; Birmingham, Patrick K.; De Oliveira, Gildasio S.
<x xml:space="preserve">Abstract</x> BACKGROUND: The caudal block is the most commonly performed regional anesthesia technique in pediatric patients undergoing surgical procedures, but safety concerns raised by previous reports remain to be addressed. Our main objective in current investigation was to estimate the overall and specific incidence of complications associated with the performance of caudal block in children. METHODS: This was an observational study using the Pediatric Regional Anesthesia Network database. A complication after a caudal block was defined by the presence of at least 1 of the following: block failure, vascular puncture, intravascular test dose, dural puncture, seizure, cardiac arrest, sacral pain, or neurologic symptoms. In addition, if a complication was also coded, the presence of temporary or permanent sequelae was evaluated. Additional exploratory analyses were performed to identify patterns of local anesthetic dosage. RESULTS: Eighteen thousand six hundred-fifty children who received a caudal block were included in the study. The overall estimated incidence (95% confidence interval [CI]) of complications after caudal blocks was 1.9% (1.7%–2.1%). Patients who developed complications were younger, median (interquartile range) of 11 (5–24) months, compared to those who did not develop any complications, 14 (7–29) months, P = 0.001. The most common complications were block failure, blood aspiration, and intravascular injection. No cases of temporary or permanent sequelae were identified leading to an estimated incidence (95% CI) of 0.005% (− % to 0.03%). Four thousand four hundred-six of 17, 867 (24.6%; 95% CI, 24%–25.2%) subjects received doses (>2 mg of bupivacaine equivalents/kg) that could be potentially unsafe. CONCLUSIONS: Safety concerns should not be a barrier to the use of caudal blocks in children assuming an appropriate selection of local anesthetic dosage.